Proceedings of the 2017 Conference on Conference Human Information Interaction and Retrieval 2017
DOI: 10.1145/3020165.3022137
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Perception of Credibility in Refugee Related Social Media Posts

Abstract: This paper describes a controlled web-based study (n=126), investigating whether the perception of the credibility of refugee-related Tweets can be influenced by cues already reported in the literature for social media content generally. We provide empirical evidence that both a Tweet's popularity and the presence of links -even neutral links created by URL shortening services -may increase a user's belief that the Tweet contains credible information. This is important because the propagation of false informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Tweets of authors with numerous followers will benefit from large amounts of likes and retweets which might also persuade readers of the quality of the posting. This is in line with results of a user study by Aigner and colleagues [16] who found that credibility ratings mainly depend on the number of retweets and likes indicating a bandwagon effect. In this way, likes and retweets can be understood as recommendations of content by other users and might be taken as an anchor for rating something as credible.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Tweets of authors with numerous followers will benefit from large amounts of likes and retweets which might also persuade readers of the quality of the posting. This is in line with results of a user study by Aigner and colleagues [16] who found that credibility ratings mainly depend on the number of retweets and likes indicating a bandwagon effect. In this way, likes and retweets can be understood as recommendations of content by other users and might be taken as an anchor for rating something as credible.…”
Section: Discussionsupporting
confidence: 91%
“…An interesting finding is presented by Aigner and colleagues [16] who conducted a study focusing on how recipients evaluate the believability of news on twitter in the area of refugee related information. They demonstrated that tweets were rated as more credible if they received a higher number of retweets and likes, and that this is even true if the tweets were factually false.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…M.J. Metzger et al [6] proposed a credibility assessment model based on Naive Bayes algorithm. J. Aigner et al [7] conducted a controlled web-based study to investigate whether the perception of the credibility of refugee-related tweets can be influenced by cues already reported in the literature for general social media contents. M. Alrubaian et al [8] proposed a model consisting of six integrated components operating in an algorithmic form to assess the credibility of tweets.…”
Section: Existing Credibility Assessment Methodsmentioning
confidence: 99%
“…(5), p(d|t) represents the probability of the distribution of document d in the case of known topic t, which can be derived from the Bayesian formula shown as Eq. (7). In order to get document-topic distribution, we multiple π and θ to get a matrix denoted as σ wihich size is M × K. Based on the definition in 3.3, the distribution π can be considered as M matrices with dimension 1 × S, while θ can be regarded as M matrices with dimension S × K. Multiplying the matrix with dimension 1 × S by the matrix with dimension S × K, a matrix with dimension 1 × K can be obtained.…”
Section: Credibility Calculation Methodsmentioning
confidence: 99%